Compliance with Corporate Governance Principles: Australian Evidence - Maryam Safari; Soheila Mirshekary; Victoria Wise (Australasian Accounting, Business and Finance Journal, 2015)
This study investigates the association between the level of compliance of Australian listed companies with Australian corporate governance principles, in aggregate, and the level of discretionary accruals using the modified Jones model. It is hypothesised that higher levels of compliance would be associated with lower levels of discretionary accruals. Data from a random sample of 214 Australian listed companies for the years 2009 and 2010 were used to test the hypothesis. The results demonstrate a significant negative relationship indicating that companies with higher levels of compliance engage in lower levels of earnings management via discretionary accruals.
Keywords: Corporate Governance; Discretionary Accruals; Earnings Management; Modified Jones Model.